ANALISIS DITERMINAN LIKUIDITAS BANK UMUM SYARIAH DENGAN UKURAN BANK SEBAGAI VARIABEL MODERATING - Fitri; Soemitra, Andri; Anggraini, Tuti (Media Ekonomi, 2023)
To analyze whether there is an influence of ROA on liquidity with bank size as a moderating variable for Sharia Banking in Indonesia. The population of this study includes annual report data from Islamic banks in Indonesia. The number of sharia banks in Indonesia in 2020 is 16 banks. The type of data used in this research is secondary data. The research method used in this research is multiple regression analysis, namely, analysis carried out to measure the magnitude of the influence of the independent variable on the dependent variable. Based on descriptive statistics regarding dependent and independent variables. Based on the results of statistical tests and discussion, the following conclusions can be drawn: CAR's effect on liquidity is moderated by bank size in Sharia banking companies in Indonesia from 2018-2022. NPF has a significant effect on liquidity, moderated by bank size in Islamic banking companies in Indonesia from 2018-2022 BOPO has a significant effect on liquidity, moderated by bank size in Islamic banking companies in Indonesia from 2018-2022. ROA has a significant effect on liquidity, moderated by bank size in Islamic banking companies in Indonesia from 2018-2022.